Diversity of Medicinal Plants for Fever Healing from Khao Phanom Benja National Park, Krabi Province - จันทรพล ปฐมา; ตันเถียร ศรายุทธ; เนียมสุวรรณ อรทัย (KKU Science Journal, 2014)
This qualitative research aimed to survey medicinal plants for fever healing from Khao Phanom Benja National Park, Krabi Province. The study had been conducted during September to November 2012. Information was obtained by semi-structured interviews with 2 key informants. The main questions included medicinal plant species, plant parts used, methods of preparation and use. The results showed that 83 species of medicinal plants for fever relief found in this study were classified into 71 genera and 47 families. Euphorbiaceae and Fabaceae were the families with the largest number of used medicinal species (8 species). The plant part most frequently used was the root. Favorite drug preparation was decoction and the most commonly used method was drinking before meals. It is indicated that there is a high diversity of medicinal plants for fever healing from Khao Phanom Benja National park. However, those are in the conserved forest, then many plant species have not been generally used. Therefore, the study would widely distribute the plant value in this area and compile local knowledge prior to disappear.